গভর্নরের স্মৃতিকথা - আহমেদ, সালেহউদ্দিন (ঢাকা : বণিকবার্তা, 2019)
Autobiographical reminiscences of Salehuddin Ahmed, b. 1949, economist and college teacher from Bangladesh.
AAL
Book Finder International, Donated By Akbar Ali Khan (38350, 38774)
In Bengali.
Keywords: Ahmed, Salehuddin, -- 1949-; Economist -- Bangladesh -- Biography; Economics; Authors, Bangladeshi -- Biography